Small peptide regulators of actin-based cell morphogenesis encoded by a polycistronic mRNA. - Kondo, T.; Hashimoto, Y.; Kato, K.; Inagaki, S.; Hayashi, S.; Kageyama, Y. (Nature Cell Biology, 2007)
Transcriptome analyses in eukaryotes, including mice and humans, have identified polyA-containing transcripts that lack long open reading frames (ORFs; >100 amino acids). These transcripts are believed most likely to function as non-coding RNAs, but their translational capacities and biological activities have not been characterized in detail. Here, we report that polished rice (pri), which was previously identified as a gene for a non-coding RNA in Drosophila, is in fact transcribed into a polycistronic mRNA that contains evolutionarily conserved short ORFs that encode 11 or 32 amino acid-long peptides. pri was expressed in all epithelial tissues during embryogenesis. The loss of pri function completely eliminated apical cuticular structures, including the epidermal denticles and tracheal taenidia, and also caused defective tracheal-tube expansion. We found that pri is essential for the formation of specific F-actin bundles that prefigures the formation of the denticles and taenidium. We provide evidences that pri acts non-cell autonomously and that four of the conserved pri ORFs are functionally redundant. These results demonstrate that pri has essential roles in epithelial morphogenesis by regulating F-actin organization.